6x + 45 + 3x = 180
9x - 45 = 180
9x = 135
x = 15
MB = 6y+26
hope it helped :D
X=6 and y=-9. Not sure if y is correct since I kind of rushed but I hope this helps!
We have the following equation:
2 (x-3) ^ 2 + 10 = 82
We must clear x.
We pass the constant terms to one side of the equation:
2 (x-3) ^ 2 = 82 - 10
2 (x-3) ^ 2 = 72
(x-3) ^ 2 = 72/2
(x-3) ^ 2 = 36
Square root to both members:
x-3 = +/- root (36)
x-3 = +/- 6
The solutions are:
x1 = 6 + 3 = 9
x2 = -6 + 3 = -3
Answer:
x1 = 9
x2 = -3
The inver of given function will be (1,-3).